Active vaccination against interleukin‐5 as long‐term treatment for insect‐bite hypersensitivity in horses. Issue 3 (25th November 2018) - Fettelschoss‐Gabriel, Antonia; Fettelschoss, Victoria; Olomski, Florian; Birkmann, Katharina; Thoms, Franziska; Bühler, Maya; Kummer, Martin; Zeltins, Andris; Kündig, Thomas M.; Bachmann, Martin F.
Abstract: Background: Insect‐bite hypersensitivity (IBH) in horses is a chronic allergic dermatitis caused by insect bites. Horses suffer from pruritic skin lesions, caused by type‐I/type‐IV allergic reactions accompanied by prominent eosinophil infiltration into the skin. Interleukin‐5 (IL‐5) is the key cytokine for eosinophils and we have previously shown that targeting IL‐5 by vaccination reduces disease symptoms in horses. Objective: Here, we analyzed the potential for long‐term therapy by assessing a second follow‐up year of the previously published study. Methods: The vaccine consisted of equine IL‐5 (eIL‐5) covalently linked to a cucumber mosaic virus‐like particle (VLP) containing a universal T cell epitope (CuMVTT ) using a semi‐crossover design to follow vaccinated horses during a second treatment season. Thirty Icelandic horses were immunized with 300 μg of eIL‐5‐CuMVTT without adjuvant. Results: The vaccine was well tolerated and did not reveal any safety concerns throughout the study. Upon vaccination, all horses developed reversible anti‐eIL‐5 auto‐antibody titers. The mean course of eosinophil levels was reduced compared to placebo treatment leading to significant reduction of clinical lesion scores. Horses in their second vaccination year showed a more pronounced improvement of disease symptoms when compared to first treatment year, most likely due to more stable antibody titers induced by a single booster injection. Hence, responses could be maintained over two seasons and the horses remained protected against disease symptoms. Conclusion: Yearly vaccination against IL‐5 may be a long‐term solution for the treatment of IBH and other eosinophil‐mediated diseases in horses and other species including humans. Abstract : Basic vaccination regimen consisting of three vaccine injections in the first treatment year induces sufficient antibody titers leading to significant improvement of insect bite hypersensitivity (IBH) lesion scores. A single booster vaccine injection in the second treatment year re‐induces anti‐IL‐5 antibody titers leading to enhanced improvement of IBH lesion scores. Anti‐IL‐5 vaccination in horses significantly reduces eosinophil levels in blood.